TINJAUAN YURIDIS TERHADAP TANGGUNG JAWAB DIREKSI DALAM KEPAILITAN PERSEROAN TERBATAS MENURUT UNDANG UNDANG NO 40 TAHUN 2007 - Siti Mahmudah (Faculty of Law, Universitas Diponegoro, 2012)
Abstract The board of director who becomes the part of the organ limited liability company (PT) , gets the responsibilities to represent PT inside or outside the court. The unpaid debts is the example of the law case that becomes the board of director’s responsibility. The unpaid debts cause bankrupted the company.The aim of this study is to know about the board of director’s responsibility in the bankruptcy of the limited liability company.The result of the study is that, the board of director’s must share the responsibility in the bankruptcy of the limiteted liability company when it because of the his mistakes and the company’s is not enough to pay the debts. Key words : Limited liability company , the board of director, bankruptcy Abstrak Direksi adalah salah satu organ PT yang bertugas untuk mewakili PT di dalam maupun diur pengadilan. Salah satu akibat dari hubungan hukum yang dilakukan direksi dalam menjalankan tugasnya adalah hutang yang belum dibayar yang dapat mengakibatkan dipailitkannya PT.Tujuan dari penulisan ini untuk mengetahui bagaimana tanggung jawab direksi terhadap kepailitan PT.Kesimpulan dari penulisan ini adalah direksi bertanggung jawab terhadap kepailitan PT apabila kepailitan tersebut dikarenakan kesalahan direksi , dan harta pailit ( PT ) tidak cukup untuk membayar seluruh kewajiban PT. Kata kunci : PT , Direksi , Kepailitan